Light activation of the dopaminergic system occurs after eye-opening in the mouse retina - Jain, Vrinda; Liang, Phillip J. M.; Raja, Sushmitha; Mikhael, Meena; Cameron, Morven A. (Frontiers in Ophthalmology, 2023)
The neuromodulator dopamine plays a significant role in light adaptation, eye growth, and modulation of neuronal circuitry in the retina. Dopaminergic amacrine cells in the adult retina release dopamine in response to light stimulation, however, the light-induced activity of these cells in during postnatal development is not known. We assessed the activity of dopaminergic amacrine cells in the retina response to a light pulse in C57BL/6 wild-type animals across various postnatal ages. Expression of tyrosine hydroxylase (TH) in dopaminergic amacrine cells was apparent from postnatal day 3 (P3) and restricted to the dorso-temporal region; by P8 TH+ cells were uniformly distributed across the retina. TH cell density increased until P8 and then markedly decreased by P10 to then remain at this density into adulthood. Light-induced c-fos expression was observed in all light-pulsed retinae, however, no c-fos was ever found to be co-localised with TH prior to P12. At P14, one day after eye opening, 100% of TH cells co-localised with c-fos and this was maintained for all older ages analysed. Dopamine and its primary metabolite DOPAC were measured in the vitreous of animals P8-P30. Both analytes were found in the vitreous at all ages, however, a significant difference in dopamine concentration between dark and light-pulsed animals was only observed at P30. DOPAC concentration was found to be significantly light-induced from P16, and the amplitude of this difference increased over time. Our data suggests that dopaminergic cell activation and light-induced dopamine release in the retina is primarily driven by classical photoreceptors after eye-opening.